Global detection and management of dysglycaemic patients with coronary artery disease results from the INTERASPIRE survey from 14 countries across six WHO regions - Safi Moayad Al-Azzawy; John William McEvoy; Isabelle Johansson; Agnieszka Adamska; Guy De Backer; Iris Erlund; Sandra Ganly; Catriona Jennings; Kornelia Kotseva; Gregory Y. H. Lip; Linda Mellbin; Kausik K. Ray; et al. (Cardiovascular Diabetology)
Abstract Objective Dysglycaemia, defined as type 2 diabetes mellitus (T2DM) or impaired glucose tolerance (IGT), increases the cardiovascular risk and prognosis. INTERASPIRE performed in 14 countries across 6 WHO regions evaluated guideline adherence and management of patients with coronary artery disease (CAD) and dysglycaemia. Methods A total of 4,548 CAD patients (18–80 years) were interviewed 6 months–2 years after hospital admission. All without diabetes were eligible for an oral glucose test (OGTT). Results Overall, 1990 (44%) had known T2DM. The OGTT revealed that 808 (40%) had previously unknown dysglycaemia (T2DM 12% and IGT 28%). Two thirds of all dysglycaemic patients were obese. A similar proportion reported low physical activity and only one third received dietary advice. Only half of dysglycemic patients were prescribed all guideline recommended cardioprotective drugs. A majority did not reach recommended blood pressure, lipids or HbA1c targets. Only 16% had attended a diabetes education program. Conclusions The INTERASPIRE study shows that screening for glucose perturbations in coronary patients is inadequate, achievement of lifestyle recommendations suboptimal and pharmacological management insufficient resulting in a poor risk factor control. Patients with coronary disease, especially those with glucose perturbations require professional support to achieve healthier lifestyles, and prescription of all cardioprotective medications to achieve guideline targets.